VD_FINDINFO Jug / 2014 / 390 vom 6. Februar 2015 - VD Tribunal cantonal (2015)
INSTANCE UNIQUE, CONCURRENCE DÉLOYALE, DEMANDE RECONVENTIONNELLE, DOMMAGE, FARDEAU DE LA PREUVE, TORT MORAL | 8 CC, 42 al. 2 CO, 49 al. 1 CO, 1 LCD, 2 LCD, 5 LCD, 9 LCD, 224 al. 1 CPC (CH), 5 al. 1 let. d CPC (CH), 58 al. 1 CPC (CH)